The difficulty of oral speech act production tasks in second language pragmatics testing - Huang, Weiying; Lu, Xiaofei (Frontiers in Psychology, 2023)
Abstract This study examined the relative difficulty of oral speech act production tasks involving eight different types of speech acts for Chinese English as a foreign language (EFL) learners and the effects of three contextual variables, namely, power, social distance, and imposition, on such difficulty. Eight Oral Discourse Completion Task items, each representing a unique combination of the three contextual variables, were designed for each speech act. Eighty Chinese EFL learners responded to these items and their responses were rated for appropriateness by two native-speaking college English instructors. A Many-facet Rasch Measurement analysis suggested that the eight speech acts can be ordered by ascending difficulty as follows: Thank, Request, Suggestion, Disagreement, Invitation, Refusal, Offer, and Apology. Significant effects on performance scores were found for the interaction between each of the three contextual variables and speech act, and the specific effects observed varied by speech act. The implications of our findings for L2 pragmatics testing are discussed.